Theoretical Studies of Corrosion Inhibition Efficiency of Two New N-Phenyl-Ethylidene-5-Bromo Isatin Derivatives - Kubba , Rehab Majed; Khathem, Mustafa Mohammed (Iraqi Journal of Science, 2022)
PM3 and DFT (B3LYP) with a 6-311++G (2d, 2p) level of theoretical quantum mechanical calculations were employed to give investigation into the inhibition efficiency of the two new N-phenyl-ethylidene-5-bromo isatin derivatives which are N-phenyl-ethylidene-5-bromo-3[(imine aceto) urea]-2-oxo indole (NPEO) and N-phenyl-ethyeidine-5-bromo-3[(imine aceto) thiourea]-2-oxo indole (NPES). The calculated physical properties and quantum chemical parameters correlated to the inhibition efficiency all are studied and discussed at the equilibrium geometry in a vacuum, dimethyl sulfoxide and aqueous at their correct symmetry.